INVESTIGATION ON GROWTH AND CHARACTERIZATION OF PURE AND TARTARIC ACID DOPED THIOUREA SINGLE CRYSTALS BY SLOW EVAPORATION TECHNIQUE (International Journal of Food and Nutritional Sciences, 2022)
The growth of single crystals of pure and Tartaric Acid (TA)-doped Thiourea (TU) was accomplished by solvent evaporation. The grown crystals were characterised by Single crystal X-ray and X-ray powder diffraction. The crystallographic data shows the TA doped crystal structure and lattice parameters was changed from the pure TU grown crystal. The powder XRD study shows that the unit cell volume of the TA doped crystal was slightly decreased from the pure grown crystals. The FTIR spectrum shows the functional groups of the pure and TA doped TU grown crystals. The EDXA analysis find elements of the formation of TA in TU.